Demystifying the way libraries support distance learning: a bibliometric analysis of scholarly communication in distance libraries - Leonidas Papachristopoulos (AAOU Journal)
Purpose – The purpose of this paper is to report on bibliometric research on the activities and services offered by distance libraries that serve distance learning institutions. Design/methodology/approach – The analysis of scholarly communication has always been a valuable tool for researchers and policymakers in order to understand trends, gaps and patterns in a specific field. In this paper, a bibliometric analysis has been applied based on a well-known bibliometric tool called “VOSviewer.” The articles that constitute the dataset of current research were drawn from two journals: the Journal of Library Administration and the Journal of Library and Information Services in Distance Learning. Findings – The bibliometric analysis applied in distance libraries showed that the researchers in this domain are mainly introverts and need to prioritize engaging in the scientific research process over merely publishing good practices. Although there are a lot of libraries serving distance learning institutions (formal and non-formal), there is a notable lack of activity in the scientific publication field. Originality/value – Distance libraries have played a significant role in supporting distance learning, and since distance education has become more important in the educational ecosystem, the analysis of its scholarly production would provide administrators, researchers and policymakers with insights for the next era of conventional libraries.